Strategi Inovatif Menggunakan Flipchart Untuk Meningkatkan Kualitas Pembelajaran Bahasa Inggris - Hesty Widiastuty; Muhamad Ario Setiawan; Muhamad Noor Fauzan; Putri Sulastri Permata Sari; Refi Komariah; Rizki Novia Darma; Syarif Hidayat (ABDIMAS TERAPAN : Jurnal Pengabdian Kepada Masyarakat Terapan, 2024)
In the era of globalization, learning English is increasingly important in education and careers. However, many teachers still experience difficulties in using flipcharts effectively in English classes. This research aims to find out whether the use of flipcharts can improve English learning outcomes and how to use flipcharts effectively in teaching English. This research was conducted at SMA NU Palangka Raya, where a training program was implemented to improve the quality of English learning using innovative media, including flipcharts. This program consists of three stages: preparation, implementation, and evaluation. The research results show that the use of flipcharts significantly increases students' understanding and participation in learning English. This research concludes that flipcharts are an effective tool for teaching English and recommends integrating flipcharts into the curriculum to increase student participation and motivation. Further evaluation is recommended to evaluate the long-term impact of innovative media on English language learning.